KONTRIBUSI KOMITMEN GURU PADA TUGAS DAN KOMUNIKASI INTERPERSONAL SECARA BERSAMA-SAMA TERHADAP IKLIM KERJA SAMA GURU SD NEGERI DI KECAMATAN JAYA BARU KOTA BANDA ACEH - Musa, Nurhaidah M. Insya; Syafrina, Alfiati (Jurnal Pesona Dasar, 2020)
Theaim of thisresearch wasto investigatedthe contributionof togetherly teacher's commitmen to interpersonal task and communication to ward state elementary school teachers collaborations ceneat Jaya Baru sub-district, city of Banda Aceh. There were 26 respondent sofel ementary steacherat Jaya Baru sub-districtmilieu, city of Banda Aceh. There sult sof this research showed that: (1) thereisrelationship between commitment (X1) and Y which significant to correlation value 0.635. It showed that commit ment have good relation ship with collaboration of teacher, (2) the correlationship between interpersonal communication (X2) and Y were significant with correlation value 0 .535. It showed that interpersonal communication hav enormal relationship with teacher's collaboration, and (3) Relationship togetherly between interpersonal commitment and communication with teacher's collaboration sceneasbigas 0.728. In other words, the relationship between the irorganization and capability 100% have not metyet requisite of being professionally teacher and to create the collaboration sphere which it should be. It alsomean that their collaboration scene isnot completeyet so that it need to bemore in creased infuturein order to getbetter quality for elementary schools at Meuraxa sub-district, city of Banda Aceh.Â